Resilience of the National Higher Education System: An Assessment, the Directions for Strengthening - Kuklin Oleg V.; Azmuk Nadiya A.; Dernova Iryna A. (Problemi Ekonomiki, 2023)
A competitive national educational system is the key to the development of the national economy, innovative growth and ensuring a decent quality of life for the population in the country. The aim of the study is to assess the resilience of the higher education system and to develop directions for post-war reform of the national higher education system on the basis of resilience. The article presents the authors’ own vision of the conception of resilience of the national system of higher education. The authors have identified and substantiated the main factors that ensure the resilience of higher education. A comprehensive characterization of the factors of resilience formation is proposed and their quantitative and qualitative parameters are analyzed. Based on the analysis of statistical data, it is defined that the national education system is sustainable and maintains its structural integrity despite the influence of destructive external factors. An important sign of resilience during martial law is academic continuity. It is found that the educational system is determined by different types of educational institutions, a wide range of educational programs, a variety of approaches to building an individual educational trajectory. It is substantiated that the national educational system is characterized by sufficient stability and diversity, but this is not a sufficient condition to ensure its resilience. The resource provision of the national system of higher education is examined. The financial resources of the educational system are emphasized and their insufficiency to ensure the resilience of the system is proved. According to the results of the correlation analysis, it is determined that there is a close relationship between the level of financing and the choice of a country of study by potential students. Based on the results of the study, directions for strengthening the resilient national system of higher education are identified. The proposed measures are systematized according to three main factors of ensuring the resilience of the educational system.